The diversity of human relationships (Cambridge, New York, 1996)
The book draws together findings from social, developmental, and organizational psychology, sociology, biology, and the research on personal relationships. It reviews the multiplicity of research approaches and results on interpersonal relationships and how they change over the life span. It also elaborates the characteristics of the different types of relationships
Keywords: interpersonal relations